2004
DOI: 10.1016/j.virol.2004.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's sarcoma-associated herpesvirus infection of blood endothelial cells induces lymphatic differentiation

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) is necessary for KS, a highly vascularized tumor predominated by endothelial-derived spindle cells that express markers of lymphatic endothelium. Following KSHV infection of TIME cells, an immortalized human dermal microvascular endothelial cell (DMVEC) line, expression of many genes specific to lymphatic endothelium, including VEGFR3, podoplanin, LYVE-1, and Prox-1, is significantly increased. Increases in VEGFR3 and podoplanin protein are also demonstrated follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
137
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(151 citation statements)
references
References 28 publications
12
137
2
Order By: Relevance
“…Despite original studies that pointed to endothelial cells as the origin of KS tumor cells 40 years ago (Dayan and Lewis 1967), the histogenetic origin of KS tumor cells has been elusive to define for many years because of the mixed gene expression profile of KS tumor cells: KS tumor cells were thought to express BEC-specific genes, but as new lymphatic research tools became available from the late 1990s, lymphatic characteristics of KS tumor cells became evident ). Later, it was found that KS's dual phenotypes of BECs and LECs were attributed to lymphatic reprogramming of BECs by KSHV (Carroll et al 2004;Hong et al 2004;Wang et al 2004): When KSHV infects BECs, it activates the expression of Prox1, the master control gene of lymphatic differentiation, and subsequently induces lymphatic reprogramming of BECs (Carroll et al 2004;Hong et al 2004;Wang et al 2004), suggesting that this oncogenic virus reactivates the otherwise silenced embryonic endothelial differentiation program in adult cells. It is not yet understood why KSHV induces the Prox1-mediated lymphatic reprogramming of vascular endothelial cells, and studies of its molecular mechanism will surely advance our understanding of endothelial cell plasticity and heterogeneity in health and disease.…”
Section: Lymphangioleiomyomatosis (Lam)mentioning
confidence: 99%
“…Despite original studies that pointed to endothelial cells as the origin of KS tumor cells 40 years ago (Dayan and Lewis 1967), the histogenetic origin of KS tumor cells has been elusive to define for many years because of the mixed gene expression profile of KS tumor cells: KS tumor cells were thought to express BEC-specific genes, but as new lymphatic research tools became available from the late 1990s, lymphatic characteristics of KS tumor cells became evident ). Later, it was found that KS's dual phenotypes of BECs and LECs were attributed to lymphatic reprogramming of BECs by KSHV (Carroll et al 2004;Hong et al 2004;Wang et al 2004): When KSHV infects BECs, it activates the expression of Prox1, the master control gene of lymphatic differentiation, and subsequently induces lymphatic reprogramming of BECs (Carroll et al 2004;Hong et al 2004;Wang et al 2004), suggesting that this oncogenic virus reactivates the otherwise silenced embryonic endothelial differentiation program in adult cells. It is not yet understood why KSHV induces the Prox1-mediated lymphatic reprogramming of vascular endothelial cells, and studies of its molecular mechanism will surely advance our understanding of endothelial cell plasticity and heterogeneity in health and disease.…”
Section: Lymphangioleiomyomatosis (Lam)mentioning
confidence: 99%
“…Wang et al, 2004). This was supported by observations that KSHV-infection of BECs led to increased expression of LEC markers such as VEGFR-3, podoplanin, LYVE-1, PROX1, VEGF-A and VEGF-C (Carroll et al, 2004;Sivakumar et al, 2008), while in parallel, KSHV infection of LECs led to increased expression of BEC markers (H.W. .…”
Section: Ks Histogenesis and The Biology Of The Ks Spindle Cellsmentioning
confidence: 62%
“…The KS spindle cells stained positive for the typical lymph endothelial markers vascular endothelial growth factor receptor (VEGFR)-3 and podoplanin (Dupin et al, 1999;Skobe et al, 1999;Weninger et al, 1999), but were negative for BEC marker (Beckstead et al, 1985;Roth et al, 1992), excluding their origin from blood vessel or hematopoietic cells. However, several further studies showed that KSHV does not only infect LECs, but also BECs (Carroll et al, 2004;Moses et al, 1999;Poole et al, 2002). Microarray analyses revealed that infection with KSHV seems to induce a cellular reprogramming of each cell type towards the gene expression profile of the other, driving these cells away from their terminally differentiated state towards the opposing lineage (Hong et al, 2004;Petrova et al, 2002;H.W.…”
Section: Ks Histogenesis and The Biology Of The Ks Spindle Cellsmentioning
confidence: 99%
“…Kaposi's sarcoma-associated herpesvirus (KSHV), also known as human herpesvirus 8, is a human gamma herpes virus that mainly infects endothelial cells and B-lymphocytes [1,2,3]. Numerous proteins encoded by the KSHV open reading frame during latency and lytic cycles of the virus have been identified, of which some are believed to transform the infected cells [1,4].…”
Section: Introductionmentioning
confidence: 99%